UPAYA MENINGKATKAN MINAT BELAJAR FISIKA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN SIKLUS (LEARNING CYCLE ”5E”) DI SMP NEGERI 1PANYABUNGAN - Darwis Darwis; Rizky Ariaji (Universitas Muhammadiyah Tapanuli Selatan, 2018)
The problem in this research is the low interest of physics student learning influence to the success of a process of physics learning. To overcome this problem, this research applied learning cycle model (Learning Cycle